Constraining the pickup ion abundance and temperature through the multifluid reconstruction of the Voyager 2 termination shock crossing. Issue 9 (26th September 2015) - Zieger, Bertalan; Opher, Merav; Tóth, Gábor; Decker, Robert B.; Richardson, John D.
Abstract Voyager 2 observations revealed that the hot solar wind ions (the so‐called pickup ions) play a dominant role in the thermodynamics of the termination shock and the heliosheath. The number density and temperature of this hot population, however, have remained unknown, since the plasma instrument on board Voyager 2 can only detect the colder thermal ion component. Here we show that due to the multifluid nature of the plasma, the fast magnetosonic mode splits into a low‐frequency fast mode and a high‐frequency fast mode. The coupling between the two fast modes results in a quasi‐stationary nonlinear wave mode, the "oscilliton, " which creates a large‐amplitude trailing wave train downstream of the thermal ion shock. By fitting multifluid shock wave solutions to the shock structure observed by Voyager 2, we are able to constrain both the abundance and the temperature of the undetected pickup ions. In our three‐fluid model, we take into account the nonnegligible partial pressure of suprathermal energetic electrons (0.022–1.5 MeV) observed by the Low‐Energy Charged Particle Experiment instrument on board Voyager 2. The best fitting simulation suggests a pickup ion abundance of 20 ± 3%, an upstream pickup ion temperature of 13.4 ± 2 MK, and a hot electron population with an apparent temperature of ~0.83 MK. We conclude that the actual shock transition is a subcritical dispersive shock wave with low Mach number and high plasma β.